Analysis of the Effect of Service Quality on Corporate Image and Service Usage Decisions at PT. Biro Klasifikasi Indonesia (Persero) - Kholick, Abdul; Kaihatu, Thomas Stefanus (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to determine the effect of service quality (X1) on corporate image (X2) and service usage decision (Y) of PT. Biro Klasifikasi Indonesia (Persero). The research approach taken is quantitative. The sampling technique used was non probability sampling with purposive sampling method. The number of samples in this study were 90 respondents with the criteria of consumers who have registered ships at PT. Biro Klasifikasi Indonesia and also has vessels registered with foreign classification agencies. The data collection method in this study used a questionnaire measured using a Likert scale and the data collected were analyzed Structural Equation Modelling with Partial Least Square. The program used is SmartPLS 3.0. Based on the results of the analysis that has been done, it is known that service quality has a positive and significant effect on the corporate image of PT. BKI, service quality has a positive and significant effect on the decision to use PT. BKI and corporate image have a positive and significant effect on the decision to use BKI.